Management of Quality Improvement for PAUD (Case Study of PAUD Handayani at Pontianak City) - Siti Ruwaidah; Wahyudi Wahyudi; Sukmawati Sukmawati (STKIP Singkawang, 2019)
The quality of education is a benchmark in assessing the success of the school in creating qualified students. It is appropriate if the school or institution can maintain and improve the quality of its education. Improving the quality of education is influenced by many factors, such as the leadership of the manager, the professionalism of the teacher, and the support of the teaching and education personnel in the institution. The purpose of this study was to obtain information about improving the quality of PAUD that focused on how planning, management, evaluation, inhibiting and supporting factors in the implementation of Handayani PAUD quality improvement, as well as efforts made to overcome the obstacles found in applying quality improvement planning. This research uses descriptive qualitative method. Data collection procedure techniques used are field research techniques while the methods used are observation, interviews, and documentation. Subjects in this study were managers, teachers, and education personnel in Handayani PAUD. The results of this study indicate that: (1) improving the quality of institutions can occur if there are plans and programs that are prepared and disseminated by joint managers of educators and education personnel and related parties, (2) management of quality improvement needs the support of all parties in the institution, (3) the evaluation of the improvement of the quality of education by the manager by supervising it periodically and continuously, and the manager should also involve the role of the supervisor to help supervise the program management in the institution, (4) the commitment of all parties in the institution is a supporting factor while less optimal evaluation from the manager, educational background of educators that are not appropriate and the professionalism of educators in carrying out the learning process is one of the inhibiting factors, and (5) the efforts made to overcome obstacles are by involving educators and education personnel in workshops or training mbingan and motivation, as well as planning to form a parenting program with parents of students around the institution's environment because the quality of education will increase and be carried out well with joint efforts, maximum control and evaluation of managers and related parties.